2012
DOI: 10.4103/0971-6203.94745
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the level of bystander effect in a couple of tumor and normal cell lines

Abstract: Radiation-induced bystander effect refers to radiation responses which occur in non-irradiated cells. The purpose of this study was to compare the level of bystander effect in a couple of tumor and normal cell lines (QU-DB and MRC5). To induce bystander effect, cells were irradiated with 0.5, 2, and 4 Gy of 60Co gamma rays and their media were transferred to non-irradiated (bystander) cells of the same type. Cells containing micronuclei were counted in bystander subgroups, non-irradiated, and 0.5 Gy irradiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…As in previous studies,[89] we found RIBE in QU-DB and MRC5 cells at doses of 0.5, 2 and 4Gy, the same doses were applied in this study. However, the same study should be performed with very low dose to find whether RIBE signal can be produced, and propagated by bystander cells at environmentally relevant low doses, similar to the present study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As in previous studies,[89] we found RIBE in QU-DB and MRC5 cells at doses of 0.5, 2 and 4Gy, the same doses were applied in this study. However, the same study should be performed with very low dose to find whether RIBE signal can be produced, and propagated by bystander cells at environmentally relevant low doses, similar to the present study.…”
Section: Discussionsupporting
confidence: 77%
“…The current study was designed to find out if the experimental results would confirm the proposed hypothesis (second order of RIBE). For this purpose, two cell lines that were able to produce bystander signals and response to them[ 8 ] were chosen. Then successive medium transfer technique was performed to induce RIBE in bystander cells.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Therefore, it was concluded that if fractionated irradiation results in the occurrence of RIBE following each fraction, it may also enhance the RIBE level when compared with an equal single dose irradiation. In other words, it is expected to observe a higher RIBE level in 4 Gy FBC (2 × 2 Gy) than in 4 Gy SBC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, different sensitivity of organs leads to different carcinogenesis risks years after exposure [38]. Different effects induced by the bystander effect in different cell types have been observed in in-vitro studies [39-41]. In-vivo studies which have confirmed the expression of carcinogenesis markers in non-targeted tissues is deemed to be different.…”
Section: Introductionmentioning
confidence: 99%